1981
DOI: 10.1148/radiology.140.2.7255704
|View full text |Cite
|
Sign up to set email alerts
|

"Semi-invasive" pulmonary aspergillosis: a new look at the spectrum of aspergillus infections of the lung.

Abstract: A chronic cavitary form of pulmonary aspergillosis may occur with mild immunosuppression or underlying lung disease. In this "semi-invasive" type, the fungus is intermediate between a simple saprophyte and an invasive pathogen. Aspergillus may produce extensive lung destruction despite the lack of vascular invasion. The absence of a previous cavity distinguishes such cases from secondary noninvasive mycetomas. Radiographic features include a chronic infiltrate, progressive cavitation, and subsequent mycetoma f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0
10

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(122 citation statements)
references
References 0 publications
3
109
0
10
Order By: Relevance
“…Severity was defined as mild, moderate and severe. The factors that were used for determining severity were (1) serum albumin value (less than 2.5 g/dl), (2) SpO 2 less than 90% or PaO 2 less than 60 Torr, (3) impaired oral administration of drugs, (4) expansion of newer infiltration shadow on chest X-ray film that was more than half of the lung field, (5) the existence of severe complications such as malignancies, cerebral vascular disorders, hepatic diseases, kidney diseases or heart failure, and (6) administration of corticosteroids. Mild severity was defined as the patient possessing none of the above factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Severity was defined as mild, moderate and severe. The factors that were used for determining severity were (1) serum albumin value (less than 2.5 g/dl), (2) SpO 2 less than 90% or PaO 2 less than 60 Torr, (3) impaired oral administration of drugs, (4) expansion of newer infiltration shadow on chest X-ray film that was more than half of the lung field, (5) the existence of severe complications such as malignancies, cerebral vascular disorders, hepatic diseases, kidney diseases or heart failure, and (6) administration of corticosteroids. Mild severity was defined as the patient possessing none of the above factors.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Several names of these chronic forms of disease have been proposed: semi-invasive aspergillosis 3 , chronic necrotizing pulmonary aspergillosis (CNPA) 4 , simple or complex aspergilloma, and chronic cavitary and fibrosing pulmonary aspergillosis (CCPA and CFPA). 5 As Hope et al 6 indicated apparently distinct entities do not exist for this syndrome and these forms usually overlap.…”
Section: Introductionmentioning
confidence: 99%
“…post-transplantation, isolation of A. fumigatus from a respiratory specimen is considered to have a high positive predictive value of invasive aspergillosis [5]. In immune-competent patients with CNPA, however, reliable diagnostic criteria are not available and histopathological confirmation cannot always be obtained [6,8]. positive results of Aspergillus precipitins.…”
Section: Nontuberculous Mycobacterial Disease H Kunst Et Almentioning
confidence: 99%
“…There may be a clinical and radiological overlap between these groups as more than one Aspergillus-related lung disease can coexist [7]. Invasive aspergillosis has been further categorised as angio-invasive and acute or chronic airway invasive aspergillosis (chronic necrotising pulmonary aspergillosis (CNPA) or semi-invasive aspergillosis) [7,8]. The former is an aggressive form of aspergillosis seen in severe immunosuppression, whereas the latter is an indolent form of invasive aspergillosis, which has been associated with NTM infection [9].…”
mentioning
confidence: 99%
“…Chronic pulmonary aspergillosis (CPA) was originally established in the early 1980s by Binder as chronic necrotizing pulmonary aspergillosis (CNPA) [1] and semi-invasive aspergillosis (SIA) by Gefter [2]. CNPA/SIA is characterized by a slow progressive cavitating process in the lungs due to Aspergillus spp.…”
Section: Introductionmentioning
confidence: 99%